Um momento decisivo do simbolismo brasileiro: a publicação de Missal e Broqueis (1893) - Simões Júnior, Alvaro Santos [UNESP] (My University, 2011)
A decisive moment of the diffusion of symbolism in Brazil was the year 1893, when were published Missal e Broquéis, first Cruz e Sousa’s symbolist works. It is important to consider the context in that those books appear and the repercussion that they provoked, because this investigation can perhaps helps to understand the reason by which the symbolism had achieved a relatively modest development in Brazil.

Um momento decisivo da difusão do simbolismo no Brasil foi o ano de 1893, quando se publicaram Missal e Broquéis, primeiras obras simbolistas de Cruz e Sousa. É importante considerar o contexto no qual esses livros surgiram e a repercussão que motivaram, porque essa investigação talvez possa ajudar a entender a razão pela qual o simbolismo alcançou um desenvolvimento relativamente modesto no Brasil.
A crucial moment of Brazilian symbolism: the publication of Missal and Broquéis (1893)
Keywords: Cruz e Sousa; Literary Criticism; Press; Symbolism; Cruz e Sousa; Crítica literária; Periódicos; Simbolismo